2011
DOI: 10.1016/j.asr.2010.05.030
|View full text |Cite
|
Sign up to set email alerts
|

The use of ionospheric tomography and elevation masks to reduce the overall error in single-frequency GPS timing applications

Abstract: Signals from Global Positioning System (GPS) satellites at the horizon or at low elevations are often excluded from a GPS solution because they experience considerable ionospheric delays and multipath effects. Their exclusion can degrade the overall satellite geometry for the calculations, resulting in greater errors; an effect known as the Dilution of Precision (DOP). In contrast, signals from high elevation satellites experience less ionospheric delays and multipath effects. The aim is to find a balance in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Interestingly, the Klobuchar time transfer is sometimes less stable than the time transfer with no correction. This concurs with the conclusions drawn by Rose et al [2011], which showed that the Klobuchar model can sometimes produce a worse result than if no ionospheric model were used at all.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Interestingly, the Klobuchar time transfer is sometimes less stable than the time transfer with no correction. This concurs with the conclusions drawn by Rose et al [2011], which showed that the Klobuchar model can sometimes produce a worse result than if no ionospheric model were used at all.…”
Section: Discussionsupporting
confidence: 91%
“…This concurs with the conclusions drawn by Rose et al . [], which showed that the Klobuchar model can sometimes produce a worse result than if no ionospheric model were used at all.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patches are identified from the output of an algorithm, the Multi-Instrument Data Assimilation System (MIDAS). MIDAS is a tomographic imaging algorithm, with a ten-year history at the time of writing (Mitchell and Spencer, 2003), that has been applied to many ionospheric studies, for example Alfonsi et al (2011), Muella et al (2011, Rose et al (2009Rose et al ( , 2011 and Yin and Mitchell (2011). It solves an under-determined four-dimensional inverse problem in order to compute a gridbased image of the electron concentration of the ionosphere in a user-selected region.…”
Section: R Burston Et Al: Automated Identification and Tracking Of mentioning
confidence: 99%
“…whilst maintaining good satellite geometry. A study done by [53] recommended that GPS timing receivers deployed in relatively mobile timing applications as presented in this thesis, are most accurate when satellites at lower elevations continue to be included with an elevation mask in the range 10 • to 20 • . It should be mentioned that it was a good thing that the GPS receiver maintained the Survey-In mode during the calibration because the GTR was designed to be portable instrument capable of dynamically determining its stationary position.…”
Section: Official Metrology Laboratory Calibration (Nmisa)mentioning
confidence: 99%